The Influence of Government Accounting Standards, Educational Level, and Utilization of Information Technology on the Quality of Financial Reports - Magribi, Robi Maulana; Ginanjar, Yogi; Mustika, Ai Lia (Finance and Business Management Journal, 2025)
Management of village funds in Indonesia still faces various challenges that hinder the effectiveness of development and highlight issues related to the utilization of funds, along with the need for high-quality village financial reports. This study aims to examine the influence of government accounting standards, educational level, and the use of information technology on the quality of financial reports. The research was conducted on all financial officials in 14 villages in Kertajati Subdistrict, Majalengka Regency. The sampling technique used was purposive sampling, resulting in 70 respondents consisting of village heads, village secretaries, and heads of divisions/sections (financial affairs, planning affairs, and governance sections). The method employed was a survey with a descriptive and verificative approach. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The results of the study indicate that government accounting standards significantly influence the quality of financial reports. The educational level of village officials also affects the quality of financial reports. Additionally, the utilization of information technology has a significant positive impact on the quality of financial reports.